2021
DOI: 10.1371/journal.pone.0246644
|View full text |Cite
|
Sign up to set email alerts
|

The presence of microorganisms in follicular fluid and its effect on the outcome of in vitro fertilization-embryo transfer (IVF-ET) treatment cycles

Abstract: Objectives To determine if the presence of microorganisms in follicular fluid of women undergoing in vitro fertilization-embryo transfer (IVF-ET) adversely affects the outcome of the treatment cycles. Methods Follicular fluid was collected from 86 women enrolled for IVF-ET at the National Hospital, Abuja from June 1, 2018 to December 1, 2018. Microscopy imaging and cultures were performed to identify bacteria and fungi in the follicular fluid and the vagina. Women with follicular fluid microorganisms were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…and Staphylococcus spp. [8,11] could be isolated from human follicular fluid samples under different media and atmospheric conditions; Staphylococcus aureus was identified in follicular fluid samples collected from post-slaughter dairy cows [14]. Our results were partly in line with the previous studies on bacteria in follicular fluid collected from humans and animals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…and Staphylococcus spp. [8,11] could be isolated from human follicular fluid samples under different media and atmospheric conditions; Staphylococcus aureus was identified in follicular fluid samples collected from post-slaughter dairy cows [14]. Our results were partly in line with the previous studies on bacteria in follicular fluid collected from humans and animals.…”
Section: Discussionsupporting
confidence: 90%
“…and Lactobacillus spp. have been cultured from follicular fluid samples in previous reports [9,11,12]. Follicular fluid samples were cultured under aerobic and anaerobic conditions for 20 days, which allowed the isolation of 23 and 33 species, respectively (Fig.…”
Section: Micro-organisms Could Be Detected In All Follicular Fluid Sa...mentioning
confidence: 99%
“…17 Contradictorily, based on another study that aimed to investigate the effect of microorganisms present in follicular fluid on IVF outcomes, bacterial colonization of follicular fluid had no effect on the number of retrieved oocytes, fertilization and pregnancy rates, and IVF outcomes. 29 Based on another research that was performed to identify and compare the microorganisms present in follicular fluid and their influence on IVF/ICSI outcomes, there was no relationship between the microorganisms present in follicular fluid and the embryo quality and the rate of pregnancy in IVF/ICSI cycles. 14 In the interpretation of the above contradictory findings, it is important to point out that currently the effect of bacteria on the oocyte is not well known and there are relatively few studies have been performed on the microorganisms present in the follicular fluid that might play a potential role in women's fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a study that aimed to investigate the influence of the microbial colonization of follicular fluid on ART outcomes, bacterial colonization in follicular fluid was associated with a decrease in the fertility rate and viable embryos in ART cycles, especially in women with endometriosis 17 . Contradictorily, based on another study that aimed to investigate the effect of microorganisms present in follicular fluid on IVF outcomes, bacterial colonization of follicular fluid had no effect on the number of retrieved oocytes, fertilization and pregnancy rates, and IVF outcomes 29 . Based on another research that was performed to identify and compare the microorganisms present in follicular fluid and their influence on IVF/ICSI outcomes, there was no relationship between the microorganisms present in follicular fluid and the embryo quality and the rate of pregnancy in IVF/ICSI cycles 14 …”
Section: Discussionmentioning
confidence: 99%
“…57 Different bacterial species have been detected in colonized follicular fluids, including Lactobacillus spp., Staphylococcus spp., and Streptococcus spp. [58][59][60] Enterococcus, 58,59 Peptostreptococcus spp., E. coli, 58,61 Mycobacterium hominis, Ureaplasma urealyticum, G. vaginalis, 60 Actinomyces spp., Propionibacterium spp., and Bifidobacterium spp. 58 A recent study identified via culturomics Streptococcus, Finegoldia, and Peptoniphilus in follicular fluid from patients undergoing IVF treatment.…”
Section: Microbial Composition Of the Ovariesmentioning
confidence: 99%